The Effect of Extensive Reading on Students’ Reading Achievement Of Senior High School - Eka Mardiana; Nur Hidayat (Kontribusia : Research Dissemination for Community Development, 2019)
The aim of this study was to investigate the effects of extensive reading on students’ reading achievement for senior high school grade X. The extensive reading was an alternative method in the teaching reading to make the students fun and easy to get the meaning of texts from many sources. The subjects were 27 students at grade X in the academic year 2018/2019. The researcher applied by using in a quasi-experimental design using a quantitative approach. The instrument of this research used pre-questionnaires, test and observation. The technique of analyzing data was applied by using a paired sample t-test from the Statistical Package for the Social Sciences 22 (SPSS22). The result of the analysis showed that the mean of the pre-test was 79, 85 and the mean of post-test was 85, 56. The mean score of posttest was higher than pretest in experimental class who were taught by extensive reading. It concluded that the implementation of the extensive reading can give positive effects to the students. It was supported by the result of observation showed that the students were enthusiastically to answer the question, many vocabularies, fun, enjoyable, easy to understand the meaning of the texts and more active in the teaching learning.